In Memory of Dr. med. vet. Gerold Sievers Prekehr (1943–2023) - Peña-Espinoza, Miguel; Muñoz, Pamela (Austral Journal of Veterinary Sciences, 2023)
Gerold Sievers Prekehr was an eminent veterinary parasitologist and former Full Professor at the Faculty of Veterinary Sciences of the Universidad Austral de Chile (UACh) in Valdivia. After obtaining his veterinary degree at the UACh, Prof. Sievers joined the University’s Veterinary Hospital as lecturer. He obtained his doctorate (Dr. med. vet.) in 1973 at the University of Veterinary Medicine Hannover (TiHo), Germany, with a thesis describing a novel method to isolate infective larvae of parasitic nematodes from pasture1. Following a period as scientist in the German pharmaceutical industry, Prof. Sievers returned to Chile in 1975 to take a position as Professor and Director of the Laboratory of Parasitology in the Institute of Animal Pathology at the UACh, roles that he held until his retirement in 2009.